Identification of the point of diminishing returns in high‐multiplicity data collection for sulfur SAD phasing. (24th November 2016) - Storm, Selina L. S.; Dall'Antonia, Fabio; Bourenkov, Gleb; Schneider, Thomas R.
Abstract : A statistic based on the distribution of sets of signed anomalous differences is evaluated as a possible metric for defining the point at which the inclusion of additional data from a progressively more damaged crystal into a S‐SAD phasing process will reduce the probability of successful phasing. Abstract : High‐quality high‐multiplicity X‐ray diffraction data were collected on five different crystals of thaumatin using a homogeneous‐profile X‐ray beam at E = 8 keV to investigate the counteracting effects of increased multiplicity and increased radiation damage on the quality of anomalous diffraction data collected on macromolecular crystals. By comparing sulfur substructures obtained from subsets of the data selected as a function of absorbed X‐ray dose with sulfur positions in the respective refined reference structures, the doses at which the highest quality of anomalous differences could be obtained were identified for the five crystals. A statistic σΔ F D, calculated as the width σ of the normalized distribution of a set Δ F of anomalous differences collected at a dose D, is suggested as a measure of anomalous data quality as a function of dose. An empirical rule is proposed to identify the dose at which the gains in data quality due to increased multiplicity are outbalanced by the losses due to decreases in signal‐to‐noise as a consequence of radiation damage. Identifying this point of diminishing returns allows the optimization of the choice of data collection parameters and the selection of data to be used in subsequent crystal structure determination steps.